2015
DOI: 10.1111/comt.12080
|View full text |Cite
|
Sign up to set email alerts
|

A Re-Explication of Social Norms, Ten Years Later

Abstract: We revisit some ideas from our previous article on social norms by conceptualizing norms as dynamic entities that both affect and are affected by human action; elaborating on the distinction between collective and perceived norms; summarizing key findings from studies that have adopted the theory of normative social behavior (TNSB) and thereby proposing guidelines for further expanding the purview of the TNSB; discussing the attribute-centered approach as a framework for focusing on behavioral characteristics;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
275
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(289 citation statements)
references
References 75 publications
10
275
0
4
Order By: Relevance
“…Therefore, we enforced one of the Asian empirical and normative expectations to be formed their motive actions in the model of "social norms" (see the definitions of Rimal and Lapinski, and see also Bicchieri,p. 41) [27,28]. This diagnostic process of identifying collective model in Asians have been discovered from our observation in a collective pattern of their behaviors.…”
Section: Discussion and Implicationsupporting
confidence: 56%
See 1 more Smart Citation
“…Therefore, we enforced one of the Asian empirical and normative expectations to be formed their motive actions in the model of "social norms" (see the definitions of Rimal and Lapinski, and see also Bicchieri,p. 41) [27,28]. This diagnostic process of identifying collective model in Asians have been discovered from our observation in a collective pattern of their behaviors.…”
Section: Discussion and Implicationsupporting
confidence: 56%
“…In examining the relationships between social norms and behaviors, Lapinski and Rimal [27] conclude that findings of the effects of social norms (which include subjective norms, injunctive norms, and descriptive norms) on behavior are mixed in normative influences. They confirmed that norms are also "dynamic phenomena and individuals, acting on either self-interest or altruistic motives, continuously alter the normative contours" in beliefs [28]. Thus, the following hypotheses are formulated to be investigated in this study.…”
Section: Normative Beliefsmentioning
confidence: 59%
“…Theoretically, it confirms previous findings of descriptive norm and injunctive norm interact to influence behavior (Rimal & Lapinski, 2015), and the practical implication is for message designing. If PSA's were to use descriptive norms in messages, it would be effective only if the element of injunctive norms was also included in the message.…”
Section: Discussionsupporting
confidence: 87%
“…However, norms literature suggest that descriptive norms influence behavioral intention , and it can moderate the relationship between intention and actual behavior (Wong & Sheth, 1985). The failure to find that moderation could be explained through the notion of behavioral attribute, which suggests that certain private behaviors are not as influenced by norms as are social behaviors (Rimal & Lapinski, 2015). Driving a motorcycles could be considered a public behavior but not so much a social one.…”
Section: Discussionmentioning
confidence: 99%
“…Traditions, like social norms are also socially negotiated, but they are more stable. The primary difference is that norms are more dynamic, and shaped and understood through communication processes 37 and can thereby be shaped to promote positive healthy behaviors 38 .…”
Section: Introductionmentioning
confidence: 99%